Initial Experience of Magnetic Resonance Imaging Fusion Biopsy in the Community Setting. Issue 1 (8th January 2021) - Krughoff, Kevin; Dagrosa, Lawrence; Seigne, John D.; Sverrisson, Einar F.; Santis, William F.; Kilchevsky, Amichai
Abstract: Introduction: Magnetic resonance imaging fusion biopsy is diagnostically superior to transrectal ultrasound guided biopsy for detecting clinically significant prostate cancer. Fusion biopsy has an expanding role at major academic centers. However, the reproducibility of outcomes in the community setting is unknown. Our goal was to determine if there are significant differences in the yield of clinically significant prostate cancer upon implementation of fusion biopsy in the community setting. Methods: We compared biopsy results from the first consecutive 175 patients undergoing fusion biopsy at an academic setting to the first 175 patients undergoing fusion biopsy at a community practice. Patients treated at an academic setting were matched to nonacademic setting treated patients using Mahalonobis distance matching. A treatment effects model was used to evaluate the effect of practice setting on the rate of clinically significant prostate cancer detection. Results: The matching model resulted in 160 community based patients matched to 150 academic based patients. Balance was verified by reduction in standardized differences and variances ratios between samples. Standard errors and the 95% CI were calculated from 3, 000 bootstrap samples. Practice setting had no significant effect on clinically significant prostate cancer detection, clinically significant prostate cancer detection by fusion biopsy, upgrading by fusion cores, upgrading by template cores, clinically significant prostate cancer missed by template cores or clinically significant prostate cancer missed by fusion cores. Conclusions: A sample-matched analysis of the first consecutive patients enrolled in fusion biopsy at an academic versus a community setting indicates that practice setting did not have a significant effect on the overall detection of clinically significant prostate cancer. This lends support to the use of fusion biopsy outside of academic centers.